Culture and brand communication: The analysis of Facebook advertisements of Volkswagen in Germany and Italy according to Hofstede’s cultural dimensions - Kasianova, Alisa; Kovács, László (HERMES - Journal of Language and Communication in Business, 2025)
The current study explores the connection between Hofstede’s cultural dimensions and advertising elements by analyzing Volkswagen’s Facebook posts targeting German and Italian consumers. For the analysis, 96 German and 57 Italian advertisements were collected from Volkswagen’s Facebook page. Texts and pictures of advertisements were analyzed using the semiotic approach, to identify how the cultural dimensions of Hofstede are present in the posts and how they reflect characteristics of the given culture. The analysis proved that German and Italian posts share certain common features; however, Volkswagen adapts the advertisements – both language and visual elements – to align with cultural expectations, balancing both universally appealing and locally relevant themes.